Designing women: gendered stereotypes in Jordanian cartoons after Arab Spring / Isra’ Mahmoud Al Jarah - Al-Jarah, Isra’ Mahmoud (2021)
The Arab spring was one of the most spiring events in the Arab world. At it, Jordan has brought to the forefront gendered ethics of existence that seeks to inscribe a vision of femininity that resists the oppressive and deterministic social roles imposed by the overarching male-controlled values and mores. Here in this paper, we will shed light on gender stereotyped pictures and weights represented by the cartoons of Emad and Osama Hajjaj. However, and emancipatory strategies have entailed the proverbial resistance to political and social praxis. Still, the issues were unclear on how to sustain the effort exerted by the inquiry of the epistemological grounds of these naturalized and rigid, oppressive constructions. Therefore, this study investigates women’s representation in the Jordanian mass media cartoons after the Arab spring. The adopted appropriate method approach through systematic phases includes compiling the selected cartoonist artwork, classification through the theme, visual analysis that integrated and compared with design thinking analysis within the aesthetic study’s data. The present study’s data consisted of portraits and pictures of two famous Jordanian cartoonists, namely, Emad and Osama Hajjaj, grouped with related data collection and analysis of the constructed images of Arab women in the Jordanian media cartoons and design. Because cartoonists may intend to stimulate multiple interpretations among readers, semantic validation is employed to evaluate the degree to which the meanings of text relative to their context are precisely represented. The study’s findings revealed several important facts that uncover these interpretations and are vital to understanding the public discourse, which means the Jordanian women. The data analysis also showed that the image and text of cartoons could significantly understand public discourse surrounding issues of the public's health and well-being. The humor's appeal in a cartoon depends on the reader’s familiarity with the cartoon's context. The cartoonists rearrange the knowledge of the broader context to construct the script of the humorous texts. More importantly, it is found that before the Arab Spring, the cartoonists drew two different types of women: the uneducated and unattractive mother and the overly sexualized woman as both objects of desire and contempt. Although the cartoonists embraced the social movement during and after the Arab Spring, tried to reflect Arab women's conditions and prospects, they did not stop using these two female stereotypes. Based upon the last words, the study recommends that women defend their rights in this world and not be influenced by the restrictions of culture or society’s beliefs. Cartoonists should do their best to represent women positively as they are half of the community.